2006
DOI: 10.1080/15563650600584402
|View full text |Cite
|
Sign up to set email alerts
|

Reimbursement Profile of a Private Toxicology Practice

Abstract: This article presents two years of billing and collection data for a bedside toxicology consultation service. The collections rate was 34% or dollars 26.19 per hour of consultative time. There was an inverse correlation between collection rates and patient acuity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 3 publications
0
8
2
Order By: Relevance
“…While other studies have found that the sickest patients received the lowest total reimbursement rate [10], we found [14]. First year faculty in this survey had mean salaries of $204,833.…”
Section: Discussioncontrasting
confidence: 82%
See 4 more Smart Citations
“…While other studies have found that the sickest patients received the lowest total reimbursement rate [10], we found [14]. First year faculty in this survey had mean salaries of $204,833.…”
Section: Discussioncontrasting
confidence: 82%
“…Medical toxicology evaluations have been reported to be extremely time-consuming with a mean time of 2.6 h for inpatient encounters and outpatient consults requiring up to 3.5 h [10]. Our average consult times, however, do not show the same time consumption with the average consult time of an inpatient consult requiring approximately 1.05 h per encounter.…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations